Optimization of CRISPR/Cas9 technique for the Ixodes ticks genome editing - Kitzberger, Daniel (Jihočeská univerzita, 2021)
CRISPR/Cas9 technique was used for genome editing of several arthropod species, but it has not yet been used on Ixodes spp. tick species. Therefore, in my work, I performed a bioinformatic analysis of the I. ricinus transcriptome and I. scapularis genome to reveal the sequence of the target gene for the CRISPR/Cas9-mediated knock-out. We prepared single guide RNA and mixed it with the Cas9 endonuclease to produce the Ribonucleoprotein complex and cleave the target sequence of the I. ricinus gene beta-galactoside alpha-2,6-sialyltransferase.
Optimization of CRISPR/Cas9 technique for the Ixodes ticks genome editing
Keywords: CRISPR/Cas9; Ixodes spp. ticks; genome editing; CRISPR; CRISPR/Cas9; Ixodes spp. ticks; genome editing; CRISPR